Islam and peacemaking in the Middle East - Funk, Nathan C. (Lynne Rienner Publishers, 2009)
Authors explore how and to what degree differences in the interpretation of Islam affect the ways in which peace is sought in the contemporary Middle East. Regional trends and case studies are analyzed. Various Islamic ideas of peace and their bearing on difficult ethnic, nationalist, and civic conflicts are highlighted. Multiple Islamic conceptions of peace and their bearing on ethnic, nationalist, and civil conflicts in the contemporary Middle East are investigated.